Extensive next-generation sequencing analysis in chronic lymphocytic leukemia at diagnosis: clinical and biological correlations. Issue 1 (December 2016) - Rigolin, Gian; Saccenti, Elena; Bassi, Cristian; Lupini, Laura; Quaglia, Francesca; Cavallari, Maurizio; Martinelli, Sara; Formigaro, Luca; Lista, Enrico; Bardi, Maria; Volta, Eleonora; Tammiso, Elisa; et al.
Abstract Background In chronic lymphocytic leukemia (CLL), next-generation sequencing (NGS) analysis represents a sensitive, reproducible, and resource-efficient technique for routine screening of gene mutations. Methods We performed an extensive biologic characterization of newly diagnosed CLL, including NGS analysis of 20 genes frequently mutated in CLL and karyotype analysis to assess whether NGS and karyotype results could be of clinical relevance in the refinement of prognosis and assessment of risk of progression. The genomic DNA from peripheral blood samples of 200 consecutive CLL patients was analyzed using Ion Torrent Personal Genome Machine, a NGS platform that uses semiconductor sequencing technology. Karyotype analysis was performed using efficient mitogens. Results Mutations were detected in 42.0 % of cases with 42.8 % of mutated patients presenting 2 or more mutations. The presence of mutations by NGS was associated with unmutatedIGHV gene (p = 0.009), CD38 positivity (p = 0.010), risk stratification by fluorescence in situ hybridization (FISH) (p < 0.001), and the complex karyotype (p = 0.003). A high risk as assessed by FISH analysis was associated with mutations affectingTP53 (p = 0.012), BIRC3 (p = 0.003), andFBXW7 (p = 0.003) while the complex karyotype was significantly associated withTP53, ATM, andMYD88 mutations (p = 0.003, 0.018, and 0.001, respectively). By multivariate analysis, the multi-hit profile (≥2 mutations by NGS) was independently associated with a shorter time to first treatment (p = 0.004) along withTP53 disruption (p = 0.040), IGHV unmutated status (p < 0.001), and advanced stage (p < 0.001). Advanced stage (p = 0.010), TP53 disruption (p < 0.001), IGHV unmutated status (p = 0.020), and the complex karyotype (p = 0.007) were independently associated with a shorter overall survival. Conclusions At diagnosis, an extensive biologic characterization including NGS and karyotype analyses using novel mitogens may offer new perspectives for a better refinement of risk stratification that could be of help in the clinical management of CLL patients.